Retained catheter during placement of dorsal root ganglion stimulator: a case report. Issue 1 (February 2019) - Kohli, Gurkirat; Amin, Shawn; Herschman, Yehuda; Mammis, Antonios
Dorsal root ganglion (DRG) stimulation is a novel therapeutic option that is being increasingly utilized for patients with neuropathic pain. The potential complications during the placement of this device remain unknown. We describe a potential complication during DRG stimulator placement not previously reported in the literature. A 50-year-old male presented to the ED with lower back pain and right lower extremity radicular pain following placement of DRG stimulator at outside facility. A fragment of an introducer catheter was retained in the spinal canal and L2-L3 neural foramen. Patient underwent L2-L3 laminectomy for removal of the catheter without any complications. DRG stimulation is an effective option for intractable neuropathic pain, but the safety of the procedure and its long-term complications need to be further investigated.